High-evaporation-heat anti-corrosion fire extinguishing agent as well as preparation method and application thereof

By adding UIO-66-F to the electronic fluorinated liquid, the problems of low efficiency and corrosiveness of existing fire extinguishing agents in lithium battery fires are solved, the preparation of anti-corrosion fire extinguishing agents with high vaporization heat is realized, and the fire extinguishing efficiency and safety are improved. properties and enhanced corrosion resistance.

CN119345653APending Publication Date: 2025-01-24JIUJIANG FIRE EQUIP CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411476318.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Existing fire extinguishing agents are inefficient in dealing with lithium battery fires, may cause fire reignition, be corrosive and may release toxic substances, affecting the safety of the environment and personnel.

Method used

Use the in-situ self-assembly reaction to prepare a nano-containing nano-organ organic hybrid material UIO-66-F, and add it to the electronic fluoride to increase the vaporization heat of fluoride and adsorb fluorine ions to form a high-vita heat anticorrosive corrosion. Fire extinguishing agent.

Benefits of technology

Improve the efficiency and safety of fire extinguishing, enhance the corrosion resistance of fluoride, avoid secondary damage to lithium batteries and equipment, and maintain the stability of fluoride fluid during long -term storage and use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005096208860000011
    Figure HDA0005096208860000011
  • Figure HDA0005096208860000012
    Figure HDA0005096208860000012
  • Figure HDA0005096208860000021
    Figure HDA0005096208860000021
Patent Text Reader

Abstract

The invention discloses a high-evaporation-heat anti-corrosion fire extinguishing agent and a preparation method and application thereof, and relates to the field of fire extinguishing agents, and the preparation method comprises the following steps: S1, mixing water and acetic acid, adding Zr (NO3) 4.5 H2O and tetrafluoroterephthalic acid, dissolving, then carrying out oil bath heating reflux, then cooling to room temperature, filtering, collecting a white product, soaking and cleaning the white product in absolute methanol, and drying, so that the high-evaporation-heat anti-corrosion fire extinguishing agent is obtained; the preparation method comprises the following steps: preparing UiO-66-F; and S2, UiO-66-F is added into the fluorinated liquid to be mixed, and the fire extinguishing agent is obtained. A fluorine-containing nano organic hybrid material UIO-66-F is prepared from a fluorine-containing organic ligand through an in-situ self-assembly reaction, and the fluorine-containing nano organic hybrid material UIO-66-F is added into an electronic fluorination liquid, so that the evaporation heat of the fluorination liquid is improved, fluorine ions of the fluorination liquid can be adsorbed, the corrosion resistance of the fluorination liquid is enhanced, and the high-evaporation-heat anti-corrosion fire extinguishing agent is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of fire extinguishing agents, and in particular to a high vaporization heat anticorrosive fire extinguishing agent and a preparation method and application thereof. Background Art

[0002] Lithium batteries have the advantages of high energy density and long cycle life, and are widely used in mobile phones, computers, new energy vehicles, etc. However, once a lithium battery catches fire, it burns violently, diffuses heat quickly, is highly toxic, and is easy to reignite. Traditional fire extinguishing agents are often difficult to effectively deal with, and may even be corrosive, causing secondary damage to electrical equipment.

[0003] Existing fire extinguishing agents have some shortcomings when dealing with lithium battery fires. For example, some fire extinguishing agents mainly extinguish fires through suffocation or isolation, and have limited inhibitory effects on the continuous high temperature reactions and chain reactions inside lithium batteries, which may cause fires to reignite. At the same time, some fire extinguishing agents may be highly corrosive and cause secondary damage to lithium batteries and their peripheral equipment. In addition, some fire extinguishing agents may release toxic substances during the fire extinguishing process, posing a threat to the environment and personnel safety. Therefore, the development of special fire extinguishing agents for lithium battery fires to improve fire extinguishing efficiency and safety has become an urgent problem to be solved.

[0004] The reason why electronic fluoride liquid is used as a special fire extinguishing agent for lithium battery fires is due to its unique physical and chemical properties. Electronic fluoride liquid has high heat of vaporization, can quickly absorb a large amount of heat, effectively reduce the battery temperature, and thus inhibit the spread of fire. At the same time, it has good insulation properties, which can ensure that no secondary disasters such as short circuits will be caused to lithium batteries and other electrical components during the fire extinguishing process. In addition, electronic fluoride liquid is also clean, safe, non-toxic and non-corrosive, and harmless to the environment and human body. Therefore, electronic fluoride liquid, as a special fire extinguishing agent for lithium battery fires, can effectively improve the efficiency and safety of fire extinguishing. However, free fluoride ions will be generated during long-term storage and application of fluoride liquid, because the fluoride molecules in the fluoride liquid will be ionized under certain conditions, releasing free-moving fluoride ions. Free fluoride ions are highly oxidizing and corrosive, and can react with many metals and oxides, causing corrosion to the corresponding systems.

[0005] In addition, as lithium batteries develop towards high integration and high energy density, increasing the heat of vaporization of the fluorinated liquid can further improve its evaporation and cooling efficiency, thereby better removing the heat generated by the equipment and ensuring rapid fire extinguishing of lithium-ion batteries. Summary of the invention

[0006] The purpose of the present invention is to solve at least one of the technical problems existing in the prior art and to provide a high vaporization heat anti-corrosion lithium battery fire extinguishing agent and a preparation method and application thereof.

[0007] The technical solution of the present invention is as follows:

[0008] The preparation method of the high vaporization heat anticorrosive lithium battery fire extinguishing agent comprises the following steps:

[0009] S1: Mix water and acetic acid, add Zr(NO3)4·5H2O and tetrafluoroterephthalic acid, heat and reflux in an oil bath after dissolving, then cool to room temperature, collect the white product by filtration, soak and wash the white product in anhydrous methanol, and dry it to obtain UiO-66-F;

[0010] S2: Add UiO-66-F to the fluorinated liquid and mix to obtain a fire extinguishing agent.

[0011] As a preferred embodiment of the present invention, in step S1, the mass ratio of Zr(NO3)4·5H2O to tetrafluoroterephthalic acid is 4-5:2-3.

[0012] As a preferred embodiment of the present invention, in step S1, the volume ratio of water to acetic acid is 5-7:3-5.

[0013] As a preferred embodiment of the present invention, in step S1, the heating reflux temperature is 303-340K, and the reflux time is 20-30h.

[0014] As a preferred embodiment of the present invention, in step S1, the cleaning time is 2-4 days.

[0015] As a preferred embodiment of the present invention, in step S1, the drying temperature is 390-400K, and the drying time is 20-30h.

[0016] As a preferred embodiment of the present invention, in step S2, the fluorinated liquid includes at least one of fluorinated ethylene glycol, fluorinated benzene, fluorinated polymer, fluorinated alkane and fluorinated alkyl acid.

[0017] As a preferred embodiment of the present invention, in step S2, the UiO-66-F accounts for 3-5wt% of the fluorination liquid; and / or;

[0018] The mixing is specifically performed by stirring at room temperature for 10-14 hours, then ultrasonicating for 30-60 minutes, with the ultrasonic temperature being ≤308K, and finally filtering.

[0019] The invention also discloses a high vaporization heat anticorrosive fire extinguishing agent, which is prepared by any of the above-mentioned preparation methods.

[0020] The invention also discloses an application of the fire extinguishing agent described above on a lithium battery.

[0021] The beneficial effects of the present invention are:

[0022] (1) The present invention uses fluorine-containing organic ligands to prepare a fluorine-based nano-organic hybrid material UIO-66-F through an in-situ self-assembly reaction. By adding it to the electronic fluorinated liquid, the vaporization heat of the fluorinated liquid is increased, and the fluorine ions of the fluorinated liquid can be adsorbed to enhance the corrosion resistance of the fluorinated liquid, thereby obtaining a high vaporization heat anti-corrosion fire extinguishing agent. Compared with other additives, UIO-66-F contains fluorine atoms, which form FF bonds with the fluorinated liquid. The interaction between the FF bonds can form a stronger non-covalent bond between UIO-66-F in the fluorinated liquid, so that UIO-66-F is evenly dispersed in the fluorinated liquid.

[0023] (2) The present invention evenly disperses UIO-66-F in the fluorinated liquid and interacts with the molecules of the fluorinated liquid. On the one hand, it can change the surface tension of the fluorinated liquid and reduce the surface energy, thereby improving the wettability and fluidity of the liquid; on the other hand, it can enhance the aggregation force between molecules. This interaction can increase the stability of the liquid, delay the evaporation process, and thus increase the heat of vaporization.

[0024] (3) The UIO-66-F of the present invention has excellent dynamic and continuous adsorption capacity for free fluoride ions in the fluoride liquid, which can prevent the fluoride liquid from being corrosive to the equipment due to the generation of fluoride ions during long-term storage and use. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 is the SEM image of UiO-66-F;

[0026] Figure 2 is the XRD pattern of UiO-66-F;

[0027] Figure 3 This is the curve of UiO-66-F addition amount and free fluoride ion adsorption rate. DETAILED DESCRIPTION

[0028] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention. If no specific techniques or conditions are specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used that do not specify the manufacturer are all conventional products that can be obtained commercially.

[0029] Example 1

[0030] (1) Preparation of UiO-66-F

[0031] 60mL of water and 40ml of acetic acid were mixed in a round-bottom flask, and 4.6g of Zr(NO3)4·5H2O and 2.4g of tetrafluoroterephthalic acid were weighed and added, and stirred to completely dissolve. Transfer to an oil bath, heat to 383K and reflux for 24h, then cool to room temperature and filter to collect the white product. Then, the obtained product was soaked in anhydrous methanol for three consecutive days at room temperature to remove the residual reagents in the pores of UiO-66-F. Finally, the product was dried in a forced air drying oven at 395K℃ for 24h.

[0032] (2) Preparation of fluorinated liquid

[0033] Take a certain amount of fluorinated liquid (perfluorohexanone), weigh 3wt% of UiO-66-F and add it, stir at room temperature for 12h, transfer to an ultrasonic cleaner, and ultrasonicate for 40 minutes, keeping the ultrasonic temperature no more than 308K. Then filter out the UiO-66-F powder deposited at the bottom of the fluorinated liquid by suction filtration to obtain the final high vaporization heat anticorrosive fluorinated liquid.

[0034] Example 2

[0035] (1) Preparation of UiO-66-F

[0036] 60mL of water and 40ml of acetic acid were mixed in a round-bottom flask, and 4.6g of Zr(NO3)4·5H2O and 2.4g of tetrafluoroterephthalic acid were weighed and added, and stirred to completely dissolve. Transfer to an oil bath, heat to 383K and reflux for 24h, then cool to room temperature and filter to collect the white product. Then, the obtained product was soaked in anhydrous methanol for three consecutive days at room temperature to remove the residual reagents in the pores of UiO-66-F. Finally, the product was dried in a forced air drying oven at 395K℃ for 24h.

[0037] (2) Preparation of fluorinated liquid

[0038] Take a certain amount of fluorinated liquid (perfluorohexanone), weigh 4wt% of UiO-66-F and add it, stir at room temperature for 12h, transfer to an ultrasonic cleaner, and ultrasonicate for 40 minutes, keeping the ultrasonic temperature no more than 308K. Then filter out the UiO-66-F powder deposited at the bottom of the fluorinated liquid by suction filtration to obtain the final high vaporization heat anticorrosive fluorinated liquid.

[0039] Example 3

[0040] (1) Preparation of UiO-66-F

[0041] 60mL of water and 40ml of acetic acid were mixed in a round-bottom flask, and 4.6g of Zr(NO3)4·5H2O and 2.4g of tetrafluoroterephthalic acid were weighed and added, and stirred to completely dissolve. Transfer to an oil bath, heat to 383K and reflux for 24h, then cool to room temperature and filter to collect the white product. Then, the obtained product was soaked in anhydrous methanol for three consecutive days at room temperature to remove the residual reagents in the pores of UiO-66-F. Finally, the product was dried in a forced air drying oven at 395K℃ for 24h.

[0042] (2) Preparation of fluorinated liquid

[0043] Take a certain amount of fluorinated liquid (perfluorohexanone), weigh 5wt% of UiO-66-F and add it, stir at room temperature for 12h, transfer to an ultrasonic cleaner, and ultrasonicate for 40 minutes, keeping the ultrasonic temperature no more than 308K. Then filter out the UiO-66-F powder deposited at the bottom of the fluorinated liquid by suction filtration to obtain the final high vaporization heat anticorrosive fluorinated liquid.

[0044] Comparative Example 1

[0045] The difference between this comparative example and Example 1 is that UiO-66-F is not added, and the fluorinated liquid (perfluorohexanone) is directly used as a comparison.

[0046] Comparative Example 2

[0047] The difference between this comparative example and Example 1 is that 1 wt % of UiO-66-F is added thereto, and the rest is the same as Example 1.

[0048] Comparative Example 3

[0049] The difference between this comparative example and Example 1 is that 2 wt % of UiO-66-F is added thereto, and the rest is the same as Example 1.

[0050] The UIO-66-F prepared in Example 1 was subjected to SEM scanning, and the results are shown in Figure 1 It can be seen that UiO-66-F has a tiny quasi-spherical structure with a particle size of 500-800nm. The formation of the small particle size structure may be the result of rapid nucleation under dynamic water reflux synthesis conditions, which is conducive to the crystal structure construction of UiO-66-F and its dispersion in fluorinated liquid.

[0051] The XRD test of UIO-66-F prepared in Example 1 is shown in Figure 2 It can be seen that UiO-66-F has typical crystal structure peaks, indicating that UiO-66-F was successfully prepared.

[0052] The above examples and comparative examples were subjected to vaporization heat measurement and free fluorine adsorption rate measurement. The measurement results are shown in Tables 1 and Figure 3 .

[0053] Table 1 Vaporization heat measurement results of examples and comparative examples

[0054] Sample Heat of vaporization (kJ / kg) Example 1 132 Example 2 138 Example 3 142 Comparative Example 1 88 Comparative Example 2 96 Comparative Example 3 112

[0055] It can be seen from Table 1 that the performance of the embodiment is better than that of the comparative example, especially higher than that of comparative examples 1 and 2. The main reason for comparative example 1 is that the embodiment prepares a fluorine-based nano-organic hybrid material UIO-66-F, which is added to the electronic fluorination liquid to increase the vaporization heat of the fluorination liquid. The main reason for comparative examples 2 and 3 is that the amount of UIO-66-F added is relatively small, which affects its vaporization heat.

[0056] In addition, from Figure 3 It can be seen that UiO-66-F has an excellent adsorption effect on free fluoride ions. When the addition amount exceeds 2%, the adsorption rate of free fluoride ions is close to 100%. It can completely adsorb the free fluoride ions in the fluoride liquid and improve the corrosion resistance of the fluoride liquid.

[0057] The above-mentioned embodiments only express the preferred implementation modes of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, various other corresponding changes and deformations can be made according to the technical solutions and concepts described above, and all these changes and deformations should fall within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a high vaporization heat anticorrosive fire extinguishing agent, characterized in that: The following steps are involved: S1: Mix water and acetic acid, add Zr(NO3)4·5H2O and tetrafluoroterephthalic acid, heat and reflux in an oil bath after dissolving, then cool to room temperature, collect the white product by filtration, soak and wash the white product in anhydrous methanol, and dry it to obtain UiO-66-F; S2: Add UiO-66-F to the fluorinated liquid and mix to obtain a fire extinguishing agent.

2. The method for preparing the high vaporization heat anticorrosive fire extinguishing agent according to claim 1, characterized in that: In step S1, the mass ratio of Zr(NO3)4·5H2O to tetrafluoroterephthalic acid is 4-5:2-3.

3. The method for preparing the high vaporization heat anticorrosive fire extinguishing agent according to claim 1, characterized in that: In step S1, the volume ratio of water to acetic acid is 5-7:3-5.

4. The method for preparing the high vaporization heat anticorrosive fire extinguishing agent according to claim 1, characterized in that: In step S1, the heating reflux temperature is 303-340K, and the reflux time is 20-30h.

5. The method for preparing the high vaporization heat anticorrosive fire extinguishing agent according to claim 1, characterized in that: In step S1, the cleaning time is 2-4 days.

6. The method for preparing the high vaporization heat anticorrosive fire extinguishing agent according to claim 1, characterized in that: In step S1, the drying temperature is 390-400K, and the drying time is 20-30h.

7. The method for preparing the high vaporization heat anticorrosive fire extinguishing agent according to claim 1, characterized in that: In step S2, the fluorinated liquid includes at least one of fluorinated ethylene glycol, fluorinated benzene, fluorinated polymer, fluorinated alkane and fluorinated alkyl acid.

8. The method for preparing the high vaporization heat anticorrosive fire extinguishing agent according to claim 1, characterized in that: In step S2, the UiO-66-F accounts for 3-5wt% of the fluorinated liquid; and / or; The mixing is specifically performed by stirring at room temperature for 10-14 hours, then ultrasonicating for 30-60 minutes, with the ultrasonic temperature being ≤308K, and finally filtering.

9. High vaporization heat anticorrosive fire extinguishing agent, characterized in that: The method is prepared by any one of claims 1 to 8.

10. Use of the fire extinguishing agent as claimed in claim 9 on lithium batteries.